Hypoxia Extends the Life Span of Vascular Smooth Muscle Cells through Telomerase Activation - Minamino, T. (American Society for Microbiology, 2001)
Chronic hypoxia induces smooth muscle cell proliferation and vessel wall remodeling in the vasculature of the lung. One well-characterized component of the hypoxic response is transcriptional activation of genes encoding vascular smooth muscle cell (VSMC) mitogens. We report here that chronic hypoxia can also prolong the growth of human VSMC by inducing telomerase activity and telomere stabilization. We demonstrate that hypoxia induced phosphorylation of the telomerase catalytic component (TERT) and sustained high levels of TERT protein expression in VSMC compared to normoxia. Furthermore, inhibition of telomerase shortened cell life span in hypoxic cultures, whereas constitutive expression of TERT extended the life span of cells under normoxic conditions. Our data indicate that hypoxic induction of telomerase activity could be involved in long-term growth of VSMC and may thus contribute to human vascular disorders.